Erschuf Gott das Gehirn oder das Gehirn Gott? - Goller, Hans (Zeitschrift für katholische Theologie, 2009)
Did God create the brain, or does the brain create God? This article evaluates the results of experimental studies on the neurobiology of religious experiences. The few existing findings depend on a very low number of subjects, and do not allow any significant conclusions. The knowledge of the neural correlates of meditative and contemplative states does not tell us anything about their content or about what it is like to be in such a state. The studies deal with extraordinary spiritual experiences which are not representative of the religious experience of the majority of believers.